Role of Vyayama in Prevention of Life Style Disoders - A Review - Priyanka Shastri,; Chandrashekaraddi S. Karamudi,; Prabhu C. Nagalapur, (International Journal of Ayurveda and Pharma Research, 2022)
Physical inactivity is a primary cause of most chronic diseases. Because nowadays we are leading a sedentary life style which in turn leads to causation of many life style diseases as well which will going to disturbs our immunity system. Swasthavritta mainly deals prevention rather curing the diseases and also which suggests the Dinacharya, Rutrucharya, Trayopatasthambha, and Vihara etc. Vyayama also eliminates all toxin of the body& increases digestive fire, physical and mental strength, also which enhances the overall well-being. So Vyayama is an important preventive, curative and rehabilitative measure. Ayurveda Science describes several types of code and conducts of Vyayama for promotion of health and also prevention of diseases. The main aim of this work is review of Vyayama according to different Ayurveda Acharya’s and to know the preventive aspect of Vyayama in different diseases.